Anquiloglosia: Complicaciones en la lactancia y fonética en pacientes pediátricos - Jaramillo Arias, Angelo Benjamín (2024)
Ankyloglossia is a relatively common congenital condition affecting the lingual frenulum, where the membrane beneath the tongue is unusually short or positioned too close to the tip of the tongue. As a result, this condition restricts tongue mobility and causes feeding difficulties, disrupting the coordination needed for effective sucking and swallowing, which makes it challenging for the infant to breastfeed properly. This study explores the primary treatment options and common complications of ankyloglossia, focusing on its impact during breastfeeding and early speech development. This study uses a bibliographic, descriptive and analytical approach, including a selection of scientific articles in English and Spanish from databases such as Medline/PubMed, Google Scholar, Scielo and Elsevier. The data collected was systematically organized into tables for subsequent analysis. Feeding difficulties are the most common complication associated with ankyloglossia, reported in 90% of cases. Other complications included problems with nipple attachment and nipple pain or damage, which occurred in 60% of cases. Low infant weight and speech difficulties, including academic challenges are observed in 50% of cases. Problems with self-esteem and self-perception and social anxiety occurred in 40% of cases. Finally, prolonged feeding times are reported in 20% of cases. Regarding treatment options for pediatric patients with ankyloglossia, most experts consider frenotomy to be the most effective treatment, with 80% support. In addition, 50% agree with the use of myofunctional therapy, while 30% favor frenectomy and 20% support speech therapy interventions. Finally, assisted breastfeeding is considered a viable option by 10% of experts. Concluding that frenotomy is a good treatment option, whit most authors agreeing with this alternative